Acoustic analysis of swallowing sounds with the use of Sonar Doppler in premature babies during food transition - Vieira, Talita Todeschini (2022)
Objective: To define the acoustic parameters and the feasibility of using swallowing acoustic analysis as an auxiliary method for the transition from nasogastric or orogastric tube feeding to oral breastfeeding. Methodology: A cross-sectional study, which consisted of the following steps: 1. Data collection: Thirty-two newborns participated in this study (16 preterm and 16 full-term); 2. Clinical speech-language pathology evaluation: Clinical data were collected using Sonar Doppler used to assess the readiness of preterm infants to start oral feeding and swallowing sounds. Swallowing sounds were captured during breastfeeding and analyzed according to the frequency, intensity, and time of swallowing, as well as the pause time between swallows and the number of swallows. Results: The control and study groups presented significant differences in the mean wave time and swallowing per minute variables. Conclusion: Sonar Doppler, as an instrument used to capture sounds, is a viable auxiliary resource to evaluate the transition from nasogastric or orogastric tube to oral breastfeeding.